Performance of Body Condition Score (BCS) and Physiological Parameters of Etawa Crossbred Goats under Intensive and Semi-Intensive Rearing Systems - Aminurrahman, Aminurrahman; Amalyadi, Rezki; Septian, I Gede Nano; Putra, Ryan Aryadin (Bulletin of Applied Animal Research, 2025)
Etawah Crossbred Goats (PE) represent a promising genetic resource for meat production due to their high adaptability and productivity. The Body Condition Score (BCS) serves as a practical indicator for assessing fat reserves and management quality, while physiological parameters such as heart rate, body temperature, and respiratory rate provide insights into animal welfare under different rearing conditions. This study aimed to evaluate the performance of BCS and physiological responses of PE goats under intensive rearing at the Teaching Farm Sandongan (Lingsar) and semi-intensive rearing at the Teaching Farm Sambik Elen (Bayan). The study was conducted from June 1–30, 2025, involving 32 goats (20 in Sandongan and 12 in Sambik Elen). BCS was assessed on a 1–5, while physiological parameters were measured between 09.00–10.00 Central Indonesian Time (WITA). Data were analyzed using a t-test at a 5% significance level. Results showed that goats in Sambik Elen had significantly higher BCS (3.6±0.49) compared to those in Sandongan (2.4±0.60) (P<0.05), reflecting differences in nutrition and management between locations. However, heart rate, body temperature, and respiratory rate did not differ significantly (P>0.05) and remained within normal physiological ranges. These findings confirm that the rearing system has a greater influence on BCS than on physiological stability, highlighting the importance of feed availability and management practices in maintaining optimal productivity of PE goats. Keywords: Body Condition Score, Physiological Parameters, Etawah Crossbred Goats, Management.